Kelayakan Usaha Agroforestry Masyarakat Sekitar Hutan Dengan Ubi Kayu Di Kabupaten Madiun - Susanto, Anang; kamal, Mustafa (JURNAL AGRI-TEK, 2015)
Forest distric area madiun regency very potential for growing cassava because most forest lands both community forests and forests belonging to the state and the surrounding area dry / marginal at the level of yields is quite high because the forest area around madiun regency become a major supplier of industrial plant cassava that are The district Ponorogo. cassava harvest is sold in fresh form, so it is still open opportunities to increase added value through the development of agro-industry potato cassava. This study aims to identify the potential of cassava and cassava market prospects are very wide open. This study was conducted using a survey method, the research locations in Madison County, district Gemarang. The research location determined by purposive with consideration that location is the center of cassava and tapioca products. Types of data collected include primary data and secondary. The results showed that in Madiun regeny Business development of marginal land utilization program by planting cassava is relatively high and the land available is quite extensive potential relative dryland farmers have been familiar with the cultivation of cassava, thus enabling the production of cassava to be developed.Keywords: land, the people, the region, cassava